2001
DOI: 10.1001/archopht.119.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the CRB1 Gene Cause Leber Congenital Amaurosis

Abstract: To test the hypothesis that mutations in the CRB1 gene cause Leber congenital amaurosis (LCA) and, if so, to describe the ocular phenotype of patients with LCA who harbor CRB1 sequence variations. Patients: One hundred ninety probands with a clinical diagnosis of LCA were selected from a cohort of 233 probands ascertained in 5 different countries. The remaining 43 probands (18%) were excluded because they harbored sequence variations in previously identified LCA genes. Methods: One hundred ninety unrelated ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
129
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(143 citation statements)
references
References 26 publications
7
129
0
7
Order By: Relevance
“…LCA with CRB1 mutations can present with white spots and pigment clumps with moderate to high hyperopia. 4 Mutations in GUCY2D and RPE65 genes are associated with normal fundus findings at birth, followed by salt and pepper appearance with varying functional outcomes. 16 In this report, we described the clinical features of a Turkish family with macular coloboma-type LCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LCA with CRB1 mutations can present with white spots and pigment clumps with moderate to high hyperopia. 4 Mutations in GUCY2D and RPE65 genes are associated with normal fundus findings at birth, followed by salt and pepper appearance with varying functional outcomes. 16 In this report, we described the clinical features of a Turkish family with macular coloboma-type LCA.…”
Section: Discussionmentioning
confidence: 99%
“…It can also present with bull's eye-type macular changes and macular coloboma-like lesions. 1 Genetic defects in GUCY2D (retinal guanylate cyclase, 17p13.1), 2 AIPL1 (aryl hydrocarbon receptor-interacting protein-like 1, 17p13.2), 3 CRB1 (Crumbs homolog 1, 1q31.3), 4 CRX (photoreceptor specific cone-rod homeobox transcription factor, 19q13.32), 5 RPE65 (retinal pigment epithelium specific 65 kDa protein, 1p31.2), 6 RPGRIP1 (retinitis pigmentosa GTPase regulator-interacting protein 1, 14q11.2), 7 RDH12 (retinal dehydrogenase 12, 14q24.1) 8 and TULP1 (Tubby-like protein 1, 6p21.31) 9 have been associated with LCA. Additionally, three independent loci with unidentified genes, LCA3 (14q24), 10 LCA5 (6q11-q16), 11 and LCA9 (1p36) 12 have been found to show linkage to LCA.…”
Section: Introductionmentioning
confidence: 99%
“…Although the nature of this role for crb is not well understood, it depends on the extracellular domain of Crb rather than on its short intracellular domain (Johnson et al, 2002). Such a role for Crb is particularly relevant as mutations in the human homologue of crb, CRB1, are associated with retinitis pigmentosa Leber's congenital amaurosis (den Hollander et al, 2001;den Hollander et al, 1999;Lotery et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in human Crumbs Homolog 1 (CRB1) are associated with the inherited retinal diseases retinitis pigmentosa 12 and Leber's congenital amaurosis (LCA) and retinal lamination defects have been observed in LCA (den Hollander et al, 1999;den Hollander et al, 2001;Lotery et al, 2001;Gerber et al, 2002;Jacobson et al, 2003). Deficiencies in mouse Crb1 are also associated with retinal abnormalities (Mehalow et al, 2003;van de Pavert et al, 2004), but these are less severe than those observed in humans, and photoreceptor development appears largely normal under normal light conditions.…”
Section: Introductionmentioning
confidence: 99%